Keratinases fromCoriolopsis byrsinaas an alternative for feather degradation: applications for cloth cleaning based on commercial detergent compatibility and for the production of collagen hydrolysate - Duffeck, Carlos Eduardo [UNESP]; Menezes, Cintia Lionela Ambrosio de [UNESP]; Boscolo, Mauricio [UNESP]; Silva, Roberto da [UNESP]; Gomes, Eleni [UNESP]; Silva, Ronivaldo Rodrigues da [UNESP] (Springer, 2020)
Objectives Keratinases are proteolytic enzymes that emerge as an alternative for dealing with the disposal of chicken feathers. In this study, we aimed to investigate the keratin-degrading enzymes secreted by the fungusCoriolopsis byrsinaand their partial biochemical characterization to adapt their use for keratin decomposition, detergent additive applications, and collagen degradation. Results We observed the secretion of different proteolytic enzymes that possessed caseinolytic activity that peaked at pH 7.0-9.0 and 60-70 degrees C and at pH 10.5 and 55-60 degrees C, and keratinolytic activity that reached a maximum at pH 7.0-7.5 and 40-55 oC and at pH 9.0 and 55 degrees C. Keratinolytic activity was maintained at approximately 63% of residual activity for 1 h at 50 degrees C. The caseinolytic activity at pH 10.5 remains stable until 1 h at 50 degrees C, and this is in contrast to the activity at pH 8.5, where the residual activity was 50%. Caseinolytic activity was inhibited only by PMSF, while keratinolytic activity was inhibited by PMSF and EDTA. When investigating the application ofC. byrsinapeptidases as an additive to commercial detergent, we observed an egg stain removal performance that was similar to that demonstrated by the commercial detergent. Conclusions Based on their activity and stability at alkaline pH, these enzymes appear to be attractive candidates for use in the detergent industry. Additionally, the collagenolytic activity of these enzymes potentially allows for their use in a wide array of industrial sectors that require collagenolytic enzymes, such as for the production of collagen hydrolysates from residues derived from the meat industry.
Keywords: Detergent; Enzyme; Keratin; Peptidase; Protease; Sustainability